Influence of Reading on Smartphone Screens on Visual Optical Quality Metrics and Tear Film Stability. Issue 10 (October 2021) - Bettach, Emmanuel; Zadok, David; Abulafia, Adi; Shoshani, Avi; Ghebali, Rony A.; Weill, Yishay; Smadja, David
Abstract : Purpose: To evaluate the impact of a prolonged reading session on a smartphone screen on optical quality metrics and tear film stability. Methods: This prospective study was conducted in 41 healthy volunteers who were asked to read an article on a smartphone screen for 20 minutes. The following tests were performed before the reading task in this consecutive order and repeated after the reading task in the same order: automated noninvasive tear break-up time, optical quality assessment including Objective Scatter Index (OSI), modulation transfer function, Strehl ratio, and tear film dynamic analysis as follows: vision break-up time (VBUT) as a function of OSI changes within 20 seconds, using a double-pass aberrometer imaging system, and fluorescein tear break-up time (FBUT) measured using the slit lamp. Results: All break-up time–related parameters (noninvasive tear break-up time, FBUT and VBUT) were significantly reduced after the reading task ( P < 0.01). The OSI was significantly worsened after the reading task ( P = 0.01), whereas all the other optical quality metrics (modulation transfer function and Strehl ratio) slightly deteriorated, were not statistically significant. A significant correlation was found between the shortening of the FBUT, VBUT, and the worsening of the OSI (r = −0.33, P < 0.05). Conclusions: A reading session on a smartphone screen in healthy subjects was found to significantly affect the tear film stability and objectively worsen the retinal image quality.